Development of Reaction Rate Lab Virtual Media in Basic Chemistry Practicum - Hayatuz Zakiyah; Dea Kumala Dewi; Etrie Jayanti; Chusnur Rahmi (Postgraduate, University of Mataram, 2023)
The Covid-19 pandemic has resulted in learning activities having to be carried out online. However, the practicum implementation was hampered due to the unavailability of virtual practicum facilities. The purpose of this study was to develop a virtual lab media for reaction rate material to determine its validity and see student responses to the media being developed. This research is research and development that adapts the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The trial was carried out on students in the 3rd semester of chemistry education at UIN Ar-Raniry. Data was collected using interview techniques and questionnaires. Interviews were conducted with chemical laboratory assistants and lecturers supporting basic chemistry practicum, product validity questionnaires were assessed by media, material and language experts, as well as student response questionnaires to find out the level of product practicality. The results showed that the developed virtual lab media obtained a validity percentage of 92.47% with very valid criteria. The test results obtained a very good response with a percentage of 86.66% and the results of the reliability test on student responses obtained a Cronbach's Alpha value = 0.910 which was greater than 0.700 meaning the questionnaire proved to be reliable. With very high validity and very good response, this virtual lab media can be used as a medium for basic chemistry practicum on reaction rate materials